Biotechnology, powerful tools for research and development (2009)
ABSTRACT: The concept of biotechnology has been in the human mind since very ancient times, when the first human beings discovered the production of wine by fermenting fruit juices, the brewing beer industry, and the conversion of milk into cheese or yogurt.  However, as these basic processes have going through a wide range of developments to supply specific requirements,  biotechnology has evolved and some of its most dramatic advances were  observed during in the last 30-years.  Modern biotechnology begins with the  ability to transfer a specific gene from one organism to another by using a set  of genetic engineering techniques, thus recombinant DNA technology sparked an era o biotech revolution.  This major achievement, together with the maintenance and growth of genetically uniform plant-and animal cell  cultures increased dramatically the spectrum of biotechnology’s applications in disease prevention, treatment and quality of life.